AGRO METEOROLOGICAL INDICES FOR BROWN SARSON (BRASSICA RAPA L.) SOWN UNDER DIFFERENT DATES OF SOWING IN TEMPERATE REGION OF KASHMIR - AKHTER, SABIA; SINGH, LAL; SAXENA, AMAL; RASOOL, RUBIA (The Bioscan, 2016)
A field experiment was conducted at KVK, Gandarbal, Shuhama, Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir during rabi season 2011-12 to study the agro meteorological indices for brown sarson (Brassica rapaL.) sown under different dates of sowing in temperate region of Kashmir. The experiment was laid out in split plot design, consisted of three dates of sowing (1st October, 15th October, 30th October) in main plot and four varieties (KOS-1, Gulchein, Shalimar Brown Sarson-1 and P-3) in sub plot replicated four times. The objective of this experiment was to study the thermal regime of brown sarson crop and its impact on phenology and yield. The results revealed that days taken to physiological maturity and yield reduced significantly with delayed sowing. 1st October sown crop had significantly higher yield, total thermal units (o C day) and the thermal use efficiency (kg ha-1/ o C day) than 15th October and 30th October sown crop while the thermal units were more or less similar in all the varieties irrespective of the date of sowing but thermal use efficiency was more with variety P-3 as compared to Shalimar Brown Sarson-1, KOS-1 and Gulchein.